2016
DOI: 10.1186/s12966-016-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of psychosocial factors in the relation between neighborhood walkability and children’s physical activity

Abstract: BackgroundThe study aimed to investigate if psychosocial factors moderate the association between objective walkability and different domains of children’s physical activity (PA). A second aim of the study was to investigate the direct associations between psychosocial factors and children’s PA. Based on previous literature, it was hypothesized that walkability would be more strongly related to PA among children with negative psychosocial profiles.MethodsData were collected between December 2011 and May 2013 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…The study of younger adults by Ding and colleagues (2012) found no significant interactions for transport walking, though there were interactions between built environment and psychosocial attributes in explaining leisure walking. The study of children’s total physical activity by D’Haese et al (2016) did not find a consistent pattern of interactions. The different patterns of findings across studies could possibly be explained by the different age groups, outcomes, and psychosocial factors explored.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The study of younger adults by Ding and colleagues (2012) found no significant interactions for transport walking, though there were interactions between built environment and psychosocial attributes in explaining leisure walking. The study of children’s total physical activity by D’Haese et al (2016) did not find a consistent pattern of interactions. The different patterns of findings across studies could possibly be explained by the different age groups, outcomes, and psychosocial factors explored.…”
Section: Discussionmentioning
confidence: 86%
“…For physical activity, few published studies with adults (Carlson et al, 2012; Ding et al, 2012; Rhodes et al, 2006; Kaczynski et al, 2012; Van Dyck et al, 2009), one study with adolecents (De Meester et al, 2013) and one study with children; (D’Haese et al, 2016)) have reported on interactions between psychosocial variables and built environments, but the patterns of interactions varied across studies. Literature on correlates of physical activity indicated built environment variables were less consistently related to youth PA than adult PA (Bauman et al, 2012), so perhaps examining multi-level interactions is more important for youth because different subgroups may respond differently to the same built environments.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires can be viewed in online supplementary file. These will include: adult and child screen-time use42–45; quality of life46–49; family co-participation in PA45; PA awareness50 51; family social norms for PA52 53; family support52; children’s and adult’s motivation for PA54 55; and children’s perceived autonomy, competence and relatedness 55…”
Section: Methods and Analysismentioning
confidence: 99%
“…Besides, regarding competitive mechanism, attitudes toward different modes also have an effect on cycling behavior, although most studies have neglected interactions between cycling attitudes and attitudes toward other travel modes. To our knowledge, only a few studies investigated the interaction effect between the built and social environment on cycling without considering cycling attitudes (Bourke et al 2018;Wang et al 2017;D'Haese et al 2016). A Belgian study on children found an interaction effect between support from friends and neighborhood walkability on cycling in leisure time (D'Haese et al 2016).…”
mentioning
confidence: 99%
“…To our knowledge, only a few studies investigated the interaction effect between the built and social environment on cycling without considering cycling attitudes (Bourke et al 2018;Wang et al 2017;D'Haese et al 2016). A Belgian study on children found an interaction effect between support from friends and neighborhood walkability on cycling in leisure time (D'Haese et al 2016). This study also showed that friend support moderated the relationship between walkability and cycling in leisure time; however the effect size of this interaction was minor.…”
mentioning
confidence: 99%